Upaya Meningkatkan Hasil Belajar Siswa pada Materi Siklus Makhluk Hidup dalam Mata Pelajaran IPA Melalui Pendekatan Kontekstual di Kelas IV SD Negeri 01 Koto Bangun Kecamatan Kapur IX - Mesrawati Mesrawati (Eduscience Development Journal, 2019)
The low student learning outcomes in class IV SD Negeri 01 Koto Bangun Kapur District IX in learning science, because science learning only uses conventional methods. Students just sit and stay listening to the teacher's explanation. The purpose of this study is to describe the use of contextual approaches to improve student learning outcomes in science learning in class IV SD Negeri 01 Koto Bangun Kapur IX District. The approach used is a qualitative and quantitative approach. This type of research is Classroom Action Research. The research was carried out based on the classroom action research step with the stages of planning, implementation, observation and reflection. Research data in the form of test results, observation of teacher and student activities, and documentation of each action to improve learning. The source of research data is the process of learning science. Data obtained from the subject studied, namely teachers and class IV students, amounting to 15 people. The results of learning science in the material cycle of living things with a contextual approach in grade IV SD 04 Koto Bangun Kapur IX District can be improved. In the first cycle the average value of 74.46 with a completeness level of 63%, increased in the second cycle the average value of students to 80.81 with a completeness level of 81%. So seen from the average obtained by students using a contextual approach to student learning outcomes can be improved. Thus, it can be concluded that the use of contextual approaches in learning Natural Sciences Cycle of Living Beings in Class IV SD Negeri 01 Koto Bangun Kapur District IX can improve student learning outcomes.